BELEZA, SEDUÇÃO E MORTE: Uma leitura exegética de Judite 16,1-12 - Marques, Maria Antônia (2008)
The canticle of Judith 16,1-12, a synthesis of the prose part of the book, reminds us of the action of the God of Israel on behalf of the oppressed, liberating them from the power of the imperial oppressors. In the centre of the poem, (v. 5) is placed the action of the All-powerful through the hand of the female. The victory of Judith is an irony not only of war, but also of women. On one side, the weapons used by the woman to kill the commander-in-chief the facial beauty, the festive dress, the sandals, the tiara in her hair , are apparently insignificant before the might of the enemy, which represent the victory of the weak over the strong. On the other hand, in a patriarchal and male-dominated society, beauty and seduction are considered as essential feminine weapons. Thus while the narrative distracts the audience, it warns the men that the beauiful woman is dangerous, and for this reason even the most powerful general can lose his head. Between the centuries 4BC and 2AD, there are many Judaic narratives which project the danger of looking at a beautiful woman. In the context of social resistence movements of the Helenistic period, to such an extent that historiographic literature accentuates the protagonism of men, whereas the action of the woman as protagonist only appears in the field of activity of fiction and furthermore to reinforce male action. To read Judith 16, 1-12 from the optic of gender challenges us to comprehend the mechanisms which continue expropriating the body and desires of women and men. It is an invitation to sing new canticles based on relations among equals in a mutual and reciprocal manner of living.(AU)